Industri Halal di Negara Berkembang dan Dominasi Malaysia Atas Negara Didalamnya - aulia, achmad mauludin (Journal of Integrative International Relations, 2024)
As a predominantly Muslim country with consistent economic development and growth rates as well as political and social stability, Malaysia is now a leader in the world's halal industry. In the State of the Global Islamic Report (SGIE) report from 2018 to 2022, Malaysia has successively led the best Islamic economic system by defeating countries with the largest Muslim populations in the world such as Indonesia, Turkey, Saudi Arabia and other major Islamic countries. Differences in government policies or strategies in managing the halal industry in Malaysia and other Muslim countries are interesting to study considering that many countries with the largest Muslim population in the world exceed Malaysia, for example, Indonesia with a percentage of Muslim population reaching 87.20%, Saudi Arabia reaching 97%, and Turkey which reached 99.20%. This study uses a descriptive descriptive method by collecting several journals and annual reports on the Global Islamic Economy. In this study, the author will discuss what is behind the Malaysian government in developing their halal industrial sector and the key factors that make Malaysia dominate the halal industry in the world.